Murtadha Muthahhari: Filsafat Etika Islam - Naibin Naibin (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
This paper discusses the thoughts of Murtadha Mutahhari about Islamic ethical philosophy. Philosophy of Islamic ethics is important to discuss as a comparison in the current discourse hegemony of Western ethics concepts. Western ethical concepts epistemologically pure concept of human, there is no role of religion and God. The concept of Western ethics has characteristics that ethics is the goal Islam has the basic ethics of religion and reason. Islamic ethics that ethics is a means